Supportive Leadership for Impact on Building Organisation Resilience - Mark Avery (ACHSM, 2024)
The health, aged and social care service sectors routinely need to deal with the consequences of stress in the delivery of care and support services; trauma; interpersonal conflict; accidents; rationing; and sustainability. For sustained and healthy functioning health workers need intrinsic and extrinsic support for resilience or the ability to maintain confident, steady and healthy functioning in response to such consequences of stress [1]. Those providing direct and indirect care [2] and those working in varied and challenging areas and location of care delivery [3] need constructs and skills to build and deal with resilience individually as well as in conjunction with collective opportunities within their organisations (teams, units, groups and organisations).....